Penggunaan Realitas Augmented untuk Pembuatan Prototipe Desain Produk: Studi Kasus pada Pengembangan Aplikasi Mobile - Setiyo Prihatmoko; Sumaryanto, Sumaryanto; Jarot Dian Susatyono (Pixel :Jurnal Ilmiah Komputer Grafis, 2024)
This research explores the use of Augmented Reality (AR) in the prototyping of product design, focusing on mobile applications for e-commerce. The aim of this study is to evaluate how AR can enhance the prototyping process in product design, improve efficiency, and facilitate better interaction between designers and end-users. The research method involves developing a mobile application prototype with AR and testing it with end-users. The results indicate that AR accelerates the design process, improves visualization accuracy, and enhances design communication. This study provides insights into the benefits and challenges of using AR in product design.